An Analysis of Politeness Principles in the Film Wadjda Based on Leech’s Theory - NH, Nurhofifah; Buana, Cahya (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2025)
Wadjda is a Saudi Arabian film directed by Haifaa al-Mansour and is the first film to be selected as the official representative of the Kingdom of Saudi Arabia at an international film festival. The dialogues in this film contain numerous instances of linguistic politeness principles. Therefore, this study aims to identify utterances that employ politeness principles and to describe the forms of those utterances. This research employs a qualitative descriptive method, with the film Wadjda as the data source. The data consist of utterances produced by the main and supporting characters that contain politeness principles. Data were collected using an observation technique, while data analysis was conducted through orthographic transcription followed by data classification based on Leech’s (1983) theory of politeness. This study applies Leech’s (1983) politeness principle, which comprises six maxims: the tact maxim, generosity maxim, modesty maxim, approbation maxim, agreement maxim, and sympathy maxim. The results reveal 13 utterances that employ politeness principles, consisting of three utterances of the tact maxim, three of the generosity maxims, three of the modesty maxims, three of the approbation maxims, one of the agreement maxims, and one of the sympathy maxims. Based on these findings, the most dominant politeness principles are the tact maxim, generosity maxim, modesty maxim, and approbation maxim. The findings of this study are consistent with the research conducted by Setiyono et al. (2021), which states that main and supporting characters tend to adhere to the tact maxim, generosity maxim, and modesty maxim.